ANALISA PENGARUH PROMOSI DAN HEDONIC MOTIVATION TERHADAP IMPULSE BUYING DI RON’S LABORATORY GALAXY MALL SURABAYA - LAURA ELISABETH TJANTOKO (Jurnal Strategi Pemasaran, 2015)
Food is a basic human needs are primary because every human need food to provide nutrients and energy to the body. This is an opportunity for business people to open the food business. It can be seen that the market of food business is getting more and more and has developed every year. One of the food business that are popular today is Ron's Laboratory. Business that specializes in desserts kind of ice cream / gelato is favored by the public. Although it has been known by the people does not mean Ron's Laboratory just remain alone, there must be a proper marketing strategy to attract the attention of consumers and consumer companies need to know what they like in order to do the right approach.This study aimed to determine the effect of promotion and hedonic motivation to impulse buying in Ron's Laboratory Galaxy Mall Surabaya. This study is a descriptive study conducted quantitative causal. This study uses PLS-SEM technique. Sample size was 100 respondents with the characteristics of young people aged 17-30 years who have ever bought ice cream / gelato Ron's Laboratory Galaxy Mall Surabaya.The results of this study indicate that the promotion effect on impulse buying and hedonic motivation effect on impulse buying.